finally, a name
Y=e^ -√x + e^3 - 2^(3x-1)
Y=e^ -x^(1/2) + e^3 - 2^(3x-1)
Y' = e^ -x^(1/2)(-1/2)x^(-1/2) + 0 - ln2(2^(3x+1))(3)
y = e^-(x^.5) + e^3 -2^(3x-1)
.5x^(-.5) e^-(x^.5) + 0 - 3[2^(3x-1)]*ln2
Answer this Question
calculus - I have been asked to solve this two different ways. The first way is...
calculus - Differentiate and do not simplify. y= e^(- sq.rt x) + e^3 - 2^(3x-1)
calculus - Differentiate and do not simplify: Y=e^-sq.rt.x + e^3 - 2^(3x-1)
calculus - Differentiate and do not simplify: Y=x^2 * 3^2x
calculus - Differentiate and simplify completely. [x^2(1-x)^3] / [(1+x)^3]
Calculus - Differentiate the following ( do not simplify) a) ln(√sinx)
trigo help! - 1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. ...
Calculus-Math - Complete the table without using the Quotient Rule. Function y=...
Calculus - I'm having problems with this one. Can't get the right answer. ...
Calculus - How do I differentiate ln (2X^2 - 12X + Y^2 -10Y) and the second ...